If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-t+6=5(-6-2t)
We move all terms to the left:
-t+6-(5(-6-2t))=0
We add all the numbers together, and all the variables
-t-(5(-2t-6))+6=0
We add all the numbers together, and all the variables
-1t-(5(-2t-6))+6=0
We calculate terms in parentheses: -(5(-2t-6)), so:We get rid of parentheses
5(-2t-6)
We multiply parentheses
-10t-30
Back to the equation:
-(-10t-30)
-1t+10t+30+6=0
We add all the numbers together, and all the variables
9t+36=0
We move all terms containing t to the left, all other terms to the right
9t=-36
t=-36/9
t=-4
| r+-18=-11 | | 11x-15=7x+33 | | 11=n/3.6 | | 12x+7=5x+71 | | 7(y-7)+2y(y+5)=16 | | 67.9=c-4.45 | | 9x=+15 | | H=-d2+12d+5 | | 3x^2+11=59 | | 8.2=y/2 | | 12-5b=15b=33-24 | | 2x+4*(x-2)=3 | | 1.4x+x=500 | | 21-x=15x-5 | | x-3.2=5.5 | | 4y=4/9 | | H=-d^2+12d+5 | | x-3.2=55 | | 55+x=150 | | X+2x=3-1 | | -86=(-8p)+2 | | x•7=16 | | 3(x+2)+2(x-1)=(5x+7) | | 2/3z+4=24-z | | -5y+6=26 | | 36=6-5b | | -6r=-2r | | -x-8=−x−8=−4x−23 | | z•7=16 | | 1=6(1—p) | | 1/2x=-3.5 | | -k-4=(-19) |